Performance comparison of packet transmission over IPv6 network on different platforms - Mohamed, S.S.; Buhari, M.S.; Saleem, H. (2006)
With the increasing popularity in recent years, many popular operating system (OS) vendors worldwide have incorporated Internet Protocol version 6 (IPv6) into their OS. The performance of the IP stack, together with the behaviour of the OS greatly affects the efficiency of network applications built on top of it. Like any other protocols, the acceptance of various IPv6 implementations heavily relies on the end-user performance. Hence, with the availability of a variety of IPv6 implementations, it is essential to evaluate their performance under different operating systems. An investigation of IPv6 stack performance on three different operating systems, namely Windows 2003, Redhat Linux 9.0 (Redhat 9.0) and FreeBSD 4.9, is discussed. Performance analysis and comparison of the three IPv6 stacks, some interesting points raised by the experimental results are addressed.